2019
DOI: 10.1063/1.5086544
|View full text |Cite
|
Sign up to set email alerts
|

Analytical gradient for the domain-based local pair natural orbital second order Møller-Plesset perturbation theory method (DLPNO-MP2)

Abstract: Building upon our previously published work [P. Pinski and F. Neese, J. Chem. Phys. 148, 031101 (2018)], we derive the formally complete analytical gradient for the domain-based local pair natural orbital second order Møller-Plesset (MP2) perturbation theory method. Extensive testing of geometry optimizations shows that the deviations from resolution of the identity-based MP2 structures are small. Covalent bond lengths are reproduced to within 0.1 pm, whereas errors in interatomic distances between noncovalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 147 publications
0
63
0
Order By: Relevance
“…Apparently, the conclusion drawn here for OSVs is applicable to that for the relaxation of PNOs. The block-diagonality condition assumed in previous PNO analytical gradients 69,70 implies only a weakly constrained relaxation of PNOs or OSVs. Summing up, the sufficient and necessary conditions by which the relaxation pair ij, arising from the residual contribution R (ij,ij) in the second term of Eq.…”
Section: Osv Relaxation As Perturbed Non-degenerate Singular Value Prmentioning
confidence: 99%
See 4 more Smart Citations
“…Apparently, the conclusion drawn here for OSVs is applicable to that for the relaxation of PNOs. The block-diagonality condition assumed in previous PNO analytical gradients 69,70 implies only a weakly constrained relaxation of PNOs or OSVs. Summing up, the sufficient and necessary conditions by which the relaxation pair ij, arising from the residual contribution R (ij,ij) in the second term of Eq.…”
Section: Osv Relaxation As Perturbed Non-degenerate Singular Value Prmentioning
confidence: 99%
“…We have chosen DTFS and RESVAN molecules out of LB12 set for which the DLPNO-MP2 optimized Si-N and S-S bond distances report quite large errors in Ref. 70 All electrons are correlated in OSV-MP2 calculations, and both OSV-MP2 geometries are well converged for three OSV-MP2 thresholds. It is observed that l osv = 10 −4.5 is necessary in order to reduce the errors below 1.0 pm.…”
Section: Bond Lengthsmentioning
confidence: 99%
See 3 more Smart Citations